Theoretical and practical aspects of the ne bis in idem principle application in the EU Law - Tubić, Bojan; Radojčić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The ne bis in idem principle as one of the most eslablished legal rules, has been widely regulated by sources of national and International Law. By its very nature, it protects individuals from double punishment for the same act, regardless of its classification as а misdemeanor, criminal offence etc. Different legal traditions, together with а purely national criminal jurisdiction, led to a certain divergency among states. Moreover, such a problem has existed for a long time in the jurisprudence of the European Court of Human Rights. However, regulation of this principle in the EU Law brought upon some novelties. In the end of 20th century and in the beginning of 21st century there was the process of a more detailed defining of conditions for the application of ne bis in idem principle. In parallel with that process, the European Court of Justice delivered its judgments, which clarified practical dillemas of national courts in this particular field of law. These judgments resulted from the requests for preliminary rulling referred by national courts. In that regard, many important precedents have been adjudicated, defining essential elements for impelmentation of prohibition of double punishment, as for example concept of the ’same act’. On the basis of the analysis of the legal framework and relevant jurisprudence of the ECJ, we come to the conclusion that the principle ne bis in idem in the EU Law system has been interpreted extensively and this fact significantly impacts on the overcomming of formalities contained in national legal systems, which can bring about double punishment for the same act.